SURVEI VO2MAX PADA ATLET PUTRA PUSAT PENDIDIKAN LATIHAN PELAJAR SULAWESI SELATAN TAHUN 2021 - Trivena Theresia Abdul Razak; Mutmainnah Mutmainnah; Hasmyati Hasmyati (Program Studi Ilmu Keolahragaan FIK UNM, 2022)
This study aims to determine how much the VO2Max level of male atheles in the training education center for South Sulawesi students in 2021. The typebog research used is descriptive quantitative research. Population and sample were South Sulawesi PPLP athletes. The sample was selected by proposive sampling technique and obtained a sample of 16 samples. The method used is a survey method with test and measurement techniques. The data abalysis technique used is statistical methods. From the data from the descriptive analysis, the value of N or the number of samples is 16 people, the mean value is 49.09, SD 4.06, the minimum value is 41.10, the maximum value is 56.50.The exercise should be of a relatively long duration but of moderate intensity. A number of studies have shown that increasing VO2Max can be achieved by exercising at a heart intensity of 65% to 85% of your maximum heart rate, for at least 20 minutes, a frequency of 3-5 times aweek. So from the above results it can be concluded that the number of athletes with very poor classification = 0 people (0%), less =(0%), enough = 3 people (18.75%), good = 8 people (50.00%), very good 4 people (25.00%) and privileged 1 person (6.25%) the difference in the results obtained was caused by severall other factors.